Reliving, Replaying Lived Experiences Through Auditory Verbal Hallucinations: Implications on Theories and Management - Vallath, Smriti; Luhrmann, Tanya; Bunders, Joske; Ravikant, Lakshmi; Gopikumar, Vandana (Frontiers in Psychiatry, 2018)
Objective: This study aims to understand the role of negative life experience (NLE) in auditory hallucinations (AHs) and explain the heterogeneity in phenomenology of auditory verbal hallucinations. Method: In depth interviews were conducted with 21 individuals (7 males and 14 females) experiencing AVHs and accessing mental health treatment services at a not-for-profit organization. Maximum variation purposive sampling technique was used to select the sample to ensure variegation is accounted for and was collected until saturation of themes was obtained. Results: Various different forms and functions of hallucinations are obtained with an evident pattern that links voices back to the NLE of the individual. Implications for therapeutic methods focusing on distress arising from said NLE is emphasized. Conclusions: The results obtained from this study implicate negative life experiences as a contributing factor in the development and maintenance of hallucinations. Sociocultural factors act as a catalyst with psychological factors creating distress and contributing to the voice-hearing experience. Treatment strategies must thus focus on content of voices and past experiences of the individual to promote recovery. A model toward conceptualization of the diversity in phenomenology is put forth.